A fourth site for Cyphelium notarisii (Physciaceae) in Spain - Hawksworth, David L. (Lazaroa, 2004)
A fourth site for Cyphelium notarisii has been found in the Picos de la Higuera in La Pedriza del Manzanares in the Sierra de Guadarama, Comunidad de Madrid. The species, which is rare in many parts of Europe, occurred on a decorticate Pinus stump amongst granite boulders. Photographs of the habitat, and photomicrographs and line drawings of the ascospores, are included. Attention is also drawn to some differences in published details of the number of cells in the ascospores and their dimensions.